Interpreting the Divine: A Post-Structuralist and Deconstructive Analysis of Waiting for Godot - Hussain, Asad; Ahmed, Wisal; Sana (Pakistan Languages and Humanities Review, 2024)
This research paper explores the concept of interpreting the divine through the lens of Post Structuralism and Deconstructivism in Samuel Beckett’s play Waiting for Godot. This study revolves around the notion that is Divine -Godot has meaningless meaning; it means there is nothing for faith on divine. Even though Divine means power of faith but Godot is not coming in play, both major characters Estragon and Valdmir and their waiting for the mysterious character Godot, whom they believe will bring them salvation. But divine becomes in play colorless, meaningless, pointless, and faithless. It investigates the representations of faith and religion in the play and its characters. This research also portrays how post structuralists depict how this text’s interpreting the divine through the Foculat and Bradth’s concept of this movement, and deconstruction theory of Derrida about the divine has special term of différance in his theory of deconstructive in play. Hence, the study contributes a deeper understanding of Backet’s selected work and explore the broader discourse on post structuralism and deconstructionism in the field of literature, and future study of Waiting for Godot suggest that belief in the divine is futile , or does the very act of waiting itself hold ethical or spiritual significance through the lens of nihilism and ethical writings.